Characterization of the paleocrusts of weathered Carboniferous volcanics from the Junggar Basin, western China: Significance as gas reservoirs. (November 2016) - Chen, Zhonghong; Liu, Wen; Zhang, Yong; Yan, Detian; Yang, Disheng; Zha, Ming; Li, Lin
Abstract: Volcanic reservoirs comprise reservoir spaces made up of pores and cracks, with secondary solution pores and tectonic-induced cracks being the most dominant. Various volcanic lithologies and lithofacies show differences in porosity and permeability because resistance to weathering differs among volcanic rock types. This study shows that among volcaniclastic rocks, volcanic breccia shows higher porosity and permeability as well as poor pore radius, sorting, and connectivity compared with volcanic tuff. Basalt and monzonitic porphyry show higher porosity and permeability compared with other volcanic lava and subvolcanic rocks. The level of porosity of different facies is in the order of effusive facies > explosive facies > subvolcanic rock facies > volcanic sedimentary facies > eruptive facies. Reservoirs show relatively high porosity and permeability near the top surface of the weathered crust. Porosity and permeability generally decrease with an increase in the distance from the Carboniferous top weathered crust. This condition indicates that weathering controls the properties of volcanic reservoirs. The distribution pattern of porosity and permeability in the weathered crust of volcanic facies differs. Strong weathering contributes to a decrease in porosity and permeability at the top part of the weathered crust. Various weathering effects on volcanic rocks control porosity and permeability vertically, and the gas accumulates mainly in the range of 0 m–200 m from the top of the weathered crust. Gas accumulation in subvolcanic and volcaniclastic rocks is better than that in volcanic lava. The log curve in geophysical exploration can help determine the vertical structure of weathered crust. The strong weathering belt shows high gamma, low electrical resistivity, low density, high neutron porosity, and high interval transit time. Highlights: Reservoir space types in the weathered Carboniferous volcanic were revealed. Changes of porosity and permeability at different volcanic were examined. Ancient volcanic reservoir property response to weathered crust layers. Porosity and permeability decrease with increasing distance to crust surface. Gas distribution depends on the weathering effect of volcanic.